Employees' knowledge of their job rights and duties and the extent of their impact on their work ethics - A survey study of the opinions of a sample of employees in the College of Administration and Economics at the University of Sulaimani - Dilman Ahmed Aziz, (The Scientific Journal of Cihan University– Sulaimaniya, 2020)
The current research aims to shed light on to which extent the employees have familiarity with their rights and duties of employees and their impact in the Job ethics in the Faculty of Administration and Economics - University of Sulaimani. After reviewing set of studies and literature, theoretical concepts and model have been designed and hypotheses were written based on the rights and duties of employees and career ethics. In order to collect data, questionnaire was designed which includes three parts (rights, duties, and ethics). (54) Questionnaires were distributed to the research sample consists of employees in the Faculty of Administration and Economics – Sulaimani University. Several tests were conducted before and after distributing the questionnaire in order to verify their validity, reliability, and to ascertain their validity in measuring the variables of the study such as the validity, reliability (Cronbach’s alpha). In order to measure the strength of regression relations between the research variables, simple and multiple linear regression analysis were applied through the use of SPSS V21, and the results showed that there is a positive effect relationship between the rights and duties of employees in their job ethics. Based on the results, a number of recommendations were given regarding the need for giving employees all their functional rights because of the impact in their job ethics